GE_GERICHTE P/20304/2014 vom 14. April 2015 - GE Cour de justice (2015)
DÉFENSE D'OFFICE ; INDEMNITÉ(EN GÉNÉRAL) ; INTÉRÊT MORATOIRE ; TARIF(EN GÉNÉRAL) ; AVOCAT ; STAGE | LPA.26; CPP.135; Cst.29; RAJ.16